2017
DOI: 10.1556/066.2017.46.1.15
|View full text |Cite
|
Sign up to set email alerts
|

Texture-modifying properties of microbial transglutaminase on 2 popular Hungarian products: Trappist cheese and frankfurter

Abstract: The aim of this study was to show how microbial transglutaminase (mTG) can be used as an effective texturemodifi er for two popular Hungarian products: Trappist cheese and frankfurter. In both cases we investigated how components of these products, milkfat in cheese and phosphate in frankfurter, can be substituted by mTG. Therefore, Trappist cheese samples were produced from cow milk of 2.8%, 3.5%, and 5% milk fat. The effect of ripening was evaluated with Texture Profi le Analysis (TPA) and sensory evaluation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 11 publications
2
4
0
Order By: Relevance
“…reported that samples treated with TGase had the most changes in their water content and hardness due to covalent bonds formed by TGase. Darnay, Králik, et al (2017)) and Darnay, Tóth, et al (2017) reported the same trend about the effect of TGase on the hardness parameter.…”
Section: Phsupporting
confidence: 54%
See 2 more Smart Citations
“…reported that samples treated with TGase had the most changes in their water content and hardness due to covalent bonds formed by TGase. Darnay, Králik, et al (2017)) and Darnay, Tóth, et al (2017) reported the same trend about the effect of TGase on the hardness parameter.…”
Section: Phsupporting
confidence: 54%
“…TGase can affect this parameter by changing the gel structure. Darnay, Králik, et al (2017) and Darnay, Tóth, et al (2017) also reported that by addition TGase to semi-hard cheese, fat content significantly (p ˂ .05) increased. In agreement with the obtained results for protein and fat content, the dry matter was increased as affected by TGase addition.…”
Section: Chemical Compositionmentioning
confidence: 84%
See 1 more Smart Citation
“…Factors that increase the efficiency of TG in cross-linking milk proteins with serum proteins in cheese production are enzyme incubation temperature and time (cross-linking time), pH, enzyme concentration, heat treatment applied to milk and the production stage in which TG is applied (Mahmood and Sebo 2009). The use of mTG in cheese varieties has been reported in many studies, but these studies have generally focussed on the effects of direct mTG addition (Hu et al 2013;Karzan et al 2016;Domagała et al 2022), the addition of different amounts of mTG (Cadavid et al 2020;Hebishy et al 2022), the presence of inactive and active mTG on cheese quality (Dmytrow et al 2010) or the improvement of textural properties in cheese (Darnay et al 2017;Danesh et al 2018). Although there are studies examining the effect of mTG addition at different times (before, after or concurrently with chymosin application) on cheese quality and yield (Mahmood and Sebo 2009;Di Pierro et al 2010;Monsalve-Atencio et al 2022), no research has been found examining the effects of the length of the enzyme application time.…”
Section: Introductionmentioning
confidence: 99%
“…2010) or the improvement of textural properties in cheese (Darnay et al . 2017; Danesh et al . 2018).…”
Section: Introductionmentioning
confidence: 99%